Morphological and phylogenetic evidence reveal three new Pseudohydnum (Auriculariales, Basidiomycota) species from North China - Zhou, Hong-Min; Bau, Tolgor; Si, Jing (Frontiers in Cellular and Infection Microbiology, 2023)
Pseudohydnum is characterized by gelatinous basidiomata with hydnoid hymenophores and longitudinally septate basidia. In this study, samples of the genus from North China were examined morphologically and phylogenetically using a dataset of the internal transcribed spacer of the ribosomal RNA gene and the nuclear large subunit rDNA. This study describes three new species, namely Pseudohydnum abietinum, Pseudohydnum candidissimum, and Pseudohydnum sinobisporum. Pseudohydnum abietinum is characterized by pileate and pale clay pink basidiomata when fresh, with a rudimentary stipe base, four-celled basidia, and broadly ellipsoid to ovoid or subglobose basidiospores (6−7.5 × 5−6.3 μm). P. candidissimum is characterized by very white basidiomata when fresh, frequently four-celled basidia, and broadly ellipsoid to subglobose basidiospores (7.2−8.5 × 6−7 μm). P. sinobisporum is characterized by ivory basidiomata when fresh, two-celled basidia, ovoid to broadly ellipsoid, or subglobose basidiospores (7.5−9.5 × 5.8−7.2 μm). The main characteristics, type localities, and hosts of Pseudohydnum species are listed.